Femoral Intramedullary Alignment in Total Knee Arthroplasty: Indications, Results, Pitfalls, Alternatives, and Controversies - Bono, Olivia J.; Olcott, Christopher W.; Carangelo, Robert; Jamison, James P.; Tigges, Russell G.; Talmo, Carl T.; Bono, James V. (The Journal of Knee Surgery, 2020)
While femoral intramedullary alignment has been found to be the most accurate and reproducible method for proper femoral component orientation in total knee arthroplasty, certain situations preclude the use of intramedullary alignment, such as ipsilateral long-stem total hip arthroplasty, femoral shaft deformity (congenital or post-traumatic), capacious femoral canal, and retained hardware. These cases require alternative alignment guides, that is, extramedullary alignment. The purpose of this study was to determine the accuracy of intramedullary alignment in reproducing the femoral anatomic axis. Using 35 adult cadaveric femora without obvious clinical deformity, and 7 with proximal prosthetic devices blocking the passage of an intramedullary guide, the accuracy of the guide rod was assessed both anatomically and radiographically. In the seven femora with proximal femoral devices, the guide rod could not be completely seated, resulting in a greater degree of flexion of the guide rod compared with the mechanical axis of the femur, and a greater degree of varus compared with the anatomical axis, as compared with 35 femora without obvious deformity. In cases where seating of the intramedullary guide rod is either incomplete or impossible, extramedullary femoral guides allow more accurate determination of the distal femoral cut by referencing directly from the mechanical axis, that is, the center of the femoral head. We present case studies as examples of indications for use of an extramedullary femoral guide. In addition, we demonstrate two different techniques for extramedullary femoral alignment using fluoroscopic guidance in cases incompatible with intramedullary alignment.
Keywords: total knee arthroplasty; femoral intramedullary alignment; extramedullary alignment; techniques